The national school of public administration in Greece: a preliminary comparative study - Vernardakis George
This preliminary study seeks to identify some of the factors responsible for the hitherto limited success fo the National School of Public Administration in Greece, which became operational in 1985. The school, modeled after the National School of Public Administration (ENA) in France, annually accepts into its four specialized tracks with their common core curriculum both civil servants and private citizens who succeed in its rigorous entrance competitions. The School represents an effort to identify administrative talent and offer specialized training in public administration toward upgrading the administrative capabilities of the Greek civil service. Some tentative conclusions point out that the limited succ
Keywords: Public Administration -- Study and Teaching -- Greece